Modeling wind and altitude effects in the 200 m sprint - Mureika, J. R. (Canadian Journal of Physics, 2003)
A quasi-realistic mathematical model of 100 m sprint performances is modified to simulate the 200 m race, a portion of which is run around a curve. The calculated effects of wind are complex functions of the wind direction and the lane in which the athlete is running. It is shown that wind and altitude-assisted marks for the 200 m are in some cases significantly higher than the corresponding adjustments for the 100 m sprint under similar conditions. The estimated advantage of a 2 m s-1 tail wind is between 0.09-0.14 s, with the greater advantage going to the runner in the outside lane. At higher altitudes (>2000 m), these corrections can rise to over 0.3 s. Crosswinds can further enhance the performance by over 0.5 s due to decreased drag forces around the curve. A consequence of these results suggests that record ratification procedures for such performances be reconsidered. The model is also used to study Michael Johnson's world record race of 19.32 s from the 1996 Olympic Games in Atlanta, Georgia.